Energy Consumption-Economic Growth Nexus: Does the Level of Aggregation Matter? - Abid, Mehdi; Sebri, Maamar (International Journal of Energy Economics and Policy, 2011)
This study investigates the causal relationship between energy consumption and economic performance for the total economy as well as for industry, transport, and residential sectors for Tunisia during the period 1980-2007. The application of Vector error correction model (VECM) for non-stationary and cointegrated series suggests that causality directions at aggregated and disaggregated levels are mixed. However, the findings have important policy implications. While at the level of the total economy, energy plays an important role in development of Tunisian economy, it seems not to have an impact on economic performance at sectoral level. We conclude that results appear to be dependent on the level of aggregation and therefore policy advices should be given with caution. Keywords: Energy sector; Economic growth; Granger causality; Vector Error Correction Models; Tunisia. JEL Classification: C01; C32; Q43